Time course of the sensitivity and specificity of anti-SARS-CoV-2 IgM and IgG antibodies for symptomatic COVID-19 in Japan - Nakano, Yuki; Kurano, Makoto; Morita, Yoshifumi; Shimura, Takuya; Yokoyama, Rin; Qian, Chungen; Xia, Fuzhen; He, Fan; Kishi, Yoshiro; Okada, Jun; Yoshikawa, Naoyuki; Nagura, Yutaka; et al. (Scientific reports, 2021)
The accurate and prompt diagnosis of SARS-CoV-2 infection is required for the control and treatment of the coronavirus infection disease 2019 (COVID-19). In this study, we aimed to investigate the time courses of the anti-severe acute corona respiratory syndrome coronavirus 2 (SARS-CoV-2) IgM and IgG titers and to evaluate the sensitivity and specificity of such tests according to the specific day after the onset of COVID-19 among a patient population in Japan. We measured the titers of SARS-CoV-2 IgM and IgG in sera from 105 subjects, including 26 symptomatic COVID-19 patients, using chemiluminescent immunoassay (CLIA) methods utilizing magnetic beads coated with SARS-CoV-2 nucleocapsid protein and spike protein. The results of a ROC analysis suggested the possibility that the cutoff values in Japan might be lower than the manufacturer’s reported cutoff (10 AU/mL): 1  AU/mL for IgM and 5  AU/mL for IgG. The sensitivity of the test before Day 8 after symptom onset was less than 50%; at Days 9–10, however, we obtained a much higher sensitivity of 81.8% for both IgM and IgG. At 15 days or later after symptom onset, the SARS-CoV-2 IgG test had a sensitivity of 100%. These results suggest that if the number of days since disease onset is taken into consideration, these antibody tests could be very useful for the diagnosis of COVID-19 and similar diseases.